The Correlation of Dhuha Prayer to the Quality of Students' Qur'an Memory in Bahrusysyifa' Qur'an Elementary School, Sukodono, Lumajang District - Ahmad Yusthru Daswara; Eka Ismaya Indra Purnamanita; Muhammad Imam Sanusi; Arifatul Ma’ani; Syovinatus Sholicha (International Journal Labs, 2022)
The purpose of this study is to analyze and further describe the Correlation of the Dhuha Prayer to the Quality of Qur'an Memorization of Students in Bahrusysyifa' Sukodono Qur'an Elementary School, Lumajang Regency. This research was carried out at SD Quba Lumajang with the subjects of the study being students of SD Quba Lumajang, as well as information from the tahfidz manager and principal. The techniques used in data collection are: questionnaire dissemination, observation, interviews, and documentation. This institution has an excellent program, namely memorization of the Qur'an where every day before starting teaching and learning activities students carry out Sunnah Dhuha prayers, therefore researchers want to find out whether there is a correlation between Dhuha prayers and the quality of memorization of the Qur'an students in the Qur'an Elementary School Bahrusyifa Sukodono Lumajang Regency. The results obtained are, the dhuha prayer correlates with the quality of memorization of the Qur'an students in the Qur'an Bahrusysyifa' Sukodono elementary school, lumajang regency. This is evidenced by the formula Chi-Square Statistics is 14.914. When evidenced by the degree of freedom (d.b = 1) a significant level of 5% greater than 3.84<14.914, this is interpreted as significant. The magnitude of the correlation of dhuha prayers to the quality of student’s memorization of the Quran obtained was 0.521. Then the value is consulted on an interpretation table that ranges from 0.400-0.600 whose interpretation value is sufficient.